2020
DOI: 10.1093/humupd/dmaa032
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of menses after functional hypothalamic amenorrhoea: if, when and why

Abstract: BACKGROUND Prolonged amenorrhoea occurs as a consequence of functional hypothalamic amenorrhoea (FHA) which is most often induced by weight loss, vigorous exercise or emotional stress. Unfortunately, removal of these triggers does not always result in the return of menses. The prevalence and conditions underlying the timing of return of menses vary strongly and some women report amenorrhoea several years after having achieved and maintained normal weight and/or energy balance. A better unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 277 publications
(432 reference statements)
1
15
0
Order By: Relevance
“…4 Although the set point for body weight at which menses are lost varies between individuals (generally BMI < 24 kg/m 2 , Table 1), intriguingly recovery of menses may require ~2 kg more than this set point and take up to 2 years after regain of normal body weight. 18 Recovery of menstrual function was observed in 86% of adolescents with AN who reached ≥90% of their ideal body weight, 19 and in 78% of women with FHA who gained weight (BMI 22 kg/m 2 in recovered vs 20 kg/ m 2 in unrecovered). 20 In summary, FHA is uncommon in overweight women, whereas both PCOS and FHA can occur in women with low/normal BMI's (Figure 1).…”
Section: Body Mass Index (Bmi)mentioning
confidence: 96%
See 1 more Smart Citation
“…4 Although the set point for body weight at which menses are lost varies between individuals (generally BMI < 24 kg/m 2 , Table 1), intriguingly recovery of menses may require ~2 kg more than this set point and take up to 2 years after regain of normal body weight. 18 Recovery of menstrual function was observed in 86% of adolescents with AN who reached ≥90% of their ideal body weight, 19 and in 78% of women with FHA who gained weight (BMI 22 kg/m 2 in recovered vs 20 kg/ m 2 in unrecovered). 20 In summary, FHA is uncommon in overweight women, whereas both PCOS and FHA can occur in women with low/normal BMI's (Figure 1).…”
Section: Body Mass Index (Bmi)mentioning
confidence: 96%
“…Furthermore, one third of athletes had amenorrhoea despite ‘normal’ BMI (21.3 ± 1.6 kg/m 2 ), 17 whereas two thirds of women with AN had amenorrhoea at a BMI between 17 and 18.9 kg/m 2 4 . Although the set point for body weight at which menses are lost varies between individuals (generally BMI < 24 kg/m 2 , Table 1), intriguingly recovery of menses may require ~2 kg more than this set point and take up to 2 years after regain of normal body weight 18 . Recovery of menstrual function was observed in 86% of adolescents with AN who reached ≥90% of their ideal body weight, 19 and in 78% of women with FHA who gained weight (BMI 22 kg/m 2 in recovered vs 20 kg/m 2 in unrecovered) 20 …”
Section: History and Examinationmentioning
confidence: 99%
“…Functional hypothalamic amenorrhea (FHA) is considered to be due to chronic anovulation without identifiable organic causes [ 1 ]. It has its direct origin in a functional decrease or stop of pulsatile Gonadotropin Releasing Hormone (GnRH) secretion, which results in insufficient ovarian function [ 1 ] and is thought to be restorable when causative behavioural factors are corrected [ 2 , 3 ]. In a very recent study on FHA and controls, Makollé et al demonstrated that the serum levels of anti-Mullerian hormone (AMH) were significantly lower in FHA patients without polycystic ovarian morphology (PCOM) than in controls [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The GnRH stimulation test has been considered a useful tool in the diagnosis of FHA [ 13 ]. Of note, despite the miscellaneous definitions of FHA which have been used in clinical studies, the GnRH stimulation test has been used only rarely [ 3 ]. This is in line with recent recommendations [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, there is a lack of established definitions of 'menstrual recovery'. Investigators have used varying definitions (Pape et al, 2020), including the occurrence of a single menses (Kopp-Woodroffe et al, 1999;Cialdella-Kam et al, 2014), positive (Guebels et al, 2014), menses followed by two menstrual cycles <36 days in length (Lagowska et al, 2014), menstrual cycles <$36 days for at least 3 months (Arends et al, 2012), and at least three menses in a 6month time period (Misra et al, 2008). In non-exercising women with FHA, recovery has been defined as occurrence of spontaneous ovulatory menstrual cycle with/without pregnancy (Falsetti et al, 2002), or menses and evidence of ovulation with E 2 >100 pg/ml and progesterone >5 ng/ml (Berga et al, 2003), whereas partial recovery has been defined as E 2 >60 pg/ml and P 4 <5 ng/ml (Berga et al, 2003).…”
Section: Discussionmentioning
confidence: 99%